The pandemic and students’ emotional well-being - Sanz Labrador, Ismael; Doncel Pedrera, Luis Miguel; Sainz González, Jorge (Razón y fe, 2022)
Confinement and the consequent closure of schools led to an increase in the proportion of children and adolescents with mental health problems from 10.9% to 16.0% in England, one of the countries for which this impact has been best measured. However, there are several aspects that would qualify this first conclusion. The first is that the experience of Spain, one of the first countries in Europe to open educational centers in a generalized and prolonged manner, shows that a significant proportion of young people recover their emotional wellbeing by returning to face-to-face classes and, with them, once again interacting with their classmates and teachers and rediscovering a space like that of schools and institutes with which they feel identified. The novel GAD3 data for Ernst & Young analyzed in this chapter show that the proportion of students with a low to very low mood decreased from 29.9% during confinement in the last quarter of the 2019-2020 academic year to 7.2% in 2020-2021 with face-to-face or blended learning. The second aspect grading the impact of the pandemic on the mental health of young people is that not all studies find that the emotional well-being of children and adolescents has worsened or at least not in all dimensions.